Hippocampal mTOR signaling is required for the antidepressant effects of paroxetine. (January 2018) - Xu, Dawei; Sun, Yuyu; Wang, Chengniu; Wang, Hao; Wang, Yingjie; Zhao, Wei; Bao, Guofeng; Wang, Fei; Cui, Zhiming; Jiang, Bo
Abstract: Although thought as a selective serotonin reuptake inhibitor (SSRI), the antidepressant mechanisms of paroxetine remain unknown. Previous studies have shown the role of the mammalian target of rapamycin (mTOR) signaling in depression. In this study, we investigated whether the antidepressant effects of paroxetine require mTOR signaling. We first examined whether chronic paroxetine administration restores the effects of CUMS and CSDS on the mTOR signaling cascade in the hippocampus and prefrontal cortex. Then, the pharmacologcial inhibitors of mTOR signaling (LY294002, U0126 and rapamycin) were used to assay if the paroxetine-induced reversing effects in the CUMS and CSDS models were prevented by mTOR system blockade. Furthermore, gene knockdown of mTOR by mTOR-shRNA was also used to test whether mTOR is necessary for the antidepressant effects of paroxetine. It was found that paroxetine treatment fully reversed the effects of CUMS and CSDS on the mTOR signaling in the hippocampus, but not the prefrontal cortex. Pharmacological inhibition of the mTOR signaling significantly blocked the antidepressant effects of paroxetine in the CUMS and CSDS models. Moreover, gene silencing of hippocampal mTOR by mTOR-shRNA also abolished the antidepressant effects of paroxetine. Taken together, hippocampal mTOR signaling is necessary for the antidepressant effects of paroxetine. Highlights: Paroxetine could reverse the effects of CUMS and CSDS on hippocampal mTOR signaling. Paroxetine does not reverse the effects of CUMS and CSDS on mTOR signaling in the prefrontal cortex. Hippocampal mTOR signaling is required for the antidepressant effects of paroxetine.